SOLUCIONES DE UN SISTEMA HIPERBÓLICO NO LINEAL CON INCLUSIÓN DE FRONTERA DIFERENCIABLE y AMORTIGUAMIENTO DE SEGUNDO ORDEN SOBRE LA FRONTERA - Perez Salvatierra, Alfonso (2008)
In this paper we study the existence of generalized solutions for a hyperbolic nonlinear system with a discontinuous multi-valued term and nonlinear second-order damping terms on the boundary.